2018
DOI: 10.6018/turismo.41.327101
|View full text |Cite
|
Sign up to set email alerts
|

Actitudes de los gerentes de los alojamientos rurales hacia el desarrollo de un turismo sostenible

Abstract: <p>La finalidad de esta investigación es identificar las actitudes e intenciones del gerente de alojamientos rurales hacia la implementación de acciones socialmente responsables, y en consecuencia hacia un turismo sostenible. El carácter novedoso radica en la conexión entre la Teoría del Comportamiento Planeado (TCP) y la Teoría del Desarrollo Sostenible. La metodología empleada es la técnica de Partial Least Square, (PLS). Los resultados evidencian que la implementación de medidas sostenibles está deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Despite this situation, there have been many recent academic studies in this field. As examples, we highlight the doctoral theses of Moral-Moral (2016), Morales-Hernández (2017), Polo-Peña (2010) and Roig-Merino (2004), and the articles by Ferrari et al (2010), García-Pozo et al (2011), Ponce-Sánchez and Canales-Martínez (2017), and Villanueva-Álvaro et al (2017) among others.…”
Section: State Of the Artmentioning
confidence: 89%
“…Despite this situation, there have been many recent academic studies in this field. As examples, we highlight the doctoral theses of Moral-Moral (2016), Morales-Hernández (2017), Polo-Peña (2010) and Roig-Merino (2004), and the articles by Ferrari et al (2010), García-Pozo et al (2011), Ponce-Sánchez and Canales-Martínez (2017), and Villanueva-Álvaro et al (2017) among others.…”
Section: State Of the Artmentioning
confidence: 89%
“…In general terms, the typology of tourism in rural areas has many common characteristics, as established by several authors [14,[25][26][27][28]. It is a type of tourism that is developed in rural areas with little massification, with a quality cultural and natural offer, linked to the rural space [29], contributing as an activity for the local development of rural areas, thus maintaining the existing population, in order to avoid a rural exodus [30,31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent research concludes that the implementation of sustainability practices by small rural tourism businesses is determined by environmental pressures, mainly from their clients. This issue is associated with the concept of social license, which stimulates the establishment of control mechanisms to evaluate the amount of social responsibility exerted and strengthens positive attitudes towards sustainable initiatives [30]. In addition, some research found that consumers that are environmentally concerned "created a common sense of responsibility and commitment that is expressed through their ethical organic food consumption and production behaviors, global environmental sensitivity, and by their actions within their communities" [31].…”
Section: Territory and Environmental Practicesmentioning
confidence: 99%